2001
DOI: 10.1109/36.921409
|View full text |Cite
|
Sign up to set email alerts
|

Development and use of a GPS ionospheric scintillation monitor

Abstract: Abstract-Besides their intended use in radionavigation, global positioning system (GPS) satellite signals provide convenient radio beacons for ionospheric studies. Among other propagation phenomena, the ionosphere affects GPS signal propagation through amplitude scintillations that develop after radio waves propagate through ionospheric electron density irregularities. This paper outlines the design, testing, and operation of a specialized GPS receiver to monitor L-band amplitude scintillations: the Cornell sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 16 publications
0
54
0
Order By: Relevance
“…Amplitude scintillation measurements used in this study were made by a scintillation monitor developed by Cornell University (Beach and Kintner 2001) and deployed in Brazil as a part of the ionospheric scintillation network of the Instituto Nacional de Pesquisas Espacias-INPE. The Cornell Scintillation Monitor (CSM or SCINTMON) was built using a GEC-Plessey GPS card with special firmware.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amplitude scintillation measurements used in this study were made by a scintillation monitor developed by Cornell University (Beach and Kintner 2001) and deployed in Brazil as a part of the ionospheric scintillation network of the Instituto Nacional de Pesquisas Espacias-INPE. The Cornell Scintillation Monitor (CSM or SCINTMON) was built using a GEC-Plessey GPS card with special firmware.…”
Section: Methodsmentioning
confidence: 99%
“…14. We must point out that the duration of a fading event depends on the velocity of the ionospheric piercing point with respect to the geomagnetic field and to the velocity of the ionospheric irregularities (Aarons et al 1980;Aarons 1982;Kintner et al 2001Kintner et al , 2004. Therefore, a non-static receiver, for instance, moving in the geomagnetic eastward direction is more likely to observe more signal fades with longer durations than those Fig.…”
Section: Fading Characteristics and Cycle Slipsmentioning
confidence: 96%
“…They reported that, for the most severe of the high-latitude storms they examined, the tracking performance of the codeless receiver was significantly degraded, although the effect on the L1 tracking performance for both types of receiver was negligible. Beach and Kintner (2001) describe the development of a GPS ionospheric scintillation monitor based on a commercially available GPS development system. Their receiver is modified to measure signal strength at a sample rate of 50 samples per second.…”
Section: Introductionmentioning
confidence: 99%
“…The digisonde data that were employed in this study were obtained at the São Luís station. The GNSS receivers are based on the GEC-Plessey GPS Builder-2 development system [Beach and Kintner, 2001] with an acquisition rate of 50 Hz and an operating frequency of 1575.42 MHz (L1 frequency). The S4 index is defined as the standard deviation of the observations of the signal intensity normalized by the received average intensity, being calculated as:…”
Section: The Scintillation Databasementioning
confidence: 99%